(untitled) (Fiep Bulletin - online, 2015)
The present work consists of a study of case of individuo of the feminine sort with 62 years that a Ischemic Cerebral Vascular Accident suffered, where looks for to point out the proposal of physical activity in such a way searching an improvement of the quality of life for this individuo in motor and psico-social aspects, for this work we use the learning of it I swim crawl, knowing that individuo suffered hemiplegia from the left side of the body. To judge if individuo had improvements in the life of this was made a daily one of field, and we always used the depositions of the husband also to give emphasis to ours we trabalho.Tivemos resulted of evolution of this individuo how much the motor aspects, cognitivos and affective such as; of improvement in the balance; improvement in the capacity to go up and to go down stairs without ofegação; an improvement of the concentration of individuo in the accomplishment of the activities proposals; a bigger confidence of individuo in accomplishment of the activities, a significant improvement of mood.